Aspects of regional rural development - Karl Fasbender (Intereconomics, 1993)
The priority previously given to urban areas by development programmes was replaced in the 1980s by efforts to implement deliberately targeted rural development. These often relatively complex projects showed less sustainable success than had been expected, however. What are the requirements for a regional rural development policy of the 1990s?
Keywords: 330; Development Strategy